Dairy product consumption and development of cancer: an overview of reviews. Issue 1 (25th January 2019) - Jeyaraman, Maya M; Abou-Setta, Ahmed M; Grant, Laurel; Farshidfar, Farnaz; Copstein, Leslie; Lys, Justin; Gottschalk, Tania; Desautels, Danielle; Czaykowski, Piotr; Pitz, Marshall; Zarychanski, Ryan
Abstract : Objectives: To provide a comprehensive systematic overview of current evidence from pooled analyses/meta-analyses and systematic reviews (PMASRs) pertaining to dairy consumption and incident cancer and/or all-cause or cancer-specific mortality. Design: Overview of reviews. Setting: Community setting. Participants: The unit of analysis is PMASRs. A total of 42 PMASRs was included in this overview of reviews. Interventions/exposures: Any dairy product consumption (eg, milk, yogurt, etc). Primary and secondary outcomes measures: Primary outcome measure is development of any type of cancer. Secondary outcome measures are all-cause mortality and cancer-specific mortality. Results: From 9693 citations identified, we included 42 PMASRs (52 study reports) published between 1991 and 2017. Thirty-one (74%) of these was pooled analyses/meta analyses, and only 11 (26%) were systematic reviews and meta-analyses. There was a wide variability in the type of study designs included within the other PMASRs, thus contributing to variable and, in instances, divergent estimates of cancer risk for several cancer subtypes. For example, only one systematic review and meta-analysis exclusively included prospective study designs. Most PMASRs were of low to moderate quality based on the Assessing the Methodological Quality of Systematic Reviews (AMSTAR) scores. The median AMSTAR score was 5 (IQR 2–7). Our overview identified conflicting evidence from PMASRs on association between dairy consumption and incident cancers or mortality. Heterogeneity in summary estimates reflected the inclusion of variable study designs and overall low methodological quality of individual PMASRs. Conclusions: The association between dairy consumption and cancer risk has been explored in PMASRs with a variety of study designs and of low to moderate quality. To fully characterise valid associations between dairy consumption and risk of cancer and/or mortality rigorously conducted, PMASRs including only high-quality prospective study designs are required. Trial registration number: CRD42017078463.